The Implementation of Fraud Prevention on the National Health Insurance at Salewangan Maros Hospital, Indonesia: A Qualitative Study - Fitri Indayani; Reza Aril Ahri; A. Rizki Amelia; Fatmah Afriyanti Gobel; Fairus Prihatin Idris (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Various fraud control methods are designed to overcome potential fraud that occurs byevery element that involved in the National Social Health Insurance System in Indonesia. This studyaims to analyze how the implementation of fraud prevention efforts that have been carried out by theNational Health Insurance (JKN) Fraud Prevention Team which was formed at the SalewanganMarosRegional Hospital. Method: This study used a descriptive qualitative approach with data collectiontechniques through in-depth interviews and observation. The informants were the Head of the ServiceDivision, the Chair of the Hospital Medical Committee, the Head of the Nursing Sub-Division, the Headof the Finance Sub-Division, and the Casemix team.Results:Efforts to increase the fraud prevention isstill weak, efforts to detect and resolve fraud are already underway, but efforts to detect fraud have notbeen continuous, detection through observation at service locations is not routinely carried out, whiledetection efforts through data analysis still rely on service data feedback obtained from BPJS, as wellas monitoring and evaluation by the Fraud Prevention Team at SalewanganMaros Regional Hospitalhas been implemented but is still very poor.Conclusion: Fraud prevention efforts must be carried outcomprehensively and involve all individuals. There must be an automated integrated system at eachservice point so that fraud prevention can be optimized.